Role of the 5-HT2A Receptor in Acute Effects of LSD on Empathy and Circulating Oxytocin - Holze, Friederike; Avedisian, Isidora; Varghese, Nimmy; Eckert, Anne; Liechti, Matthias E. (Frontiers in Pharmacology, 2021)
The psychedelic lysergic acid diethylamide (LSD) has experienced a revival in research, including clinical trials that evaluate LSD-assisted psychotherapy. LSD induces perceptual alterations and influences emotion processing in ways that may support psychotherapy. Here, we investigated the effects of LSD on emotional empathy and mediating role of the serotonin 5-hydroxytryptamine-2A (5-HT2A) receptor by administering 25, 50, 100, and 200 µg LSD alone and 200 µg LSD combined with pretreatment with the 5-HT2A receptor antagonist ketanserin (40 mg) using a placebo-controlled, double-blind, random-order, crossover design in 16 healthy subjects. The Multifaceted Empathy Test (MET) was used to assess the effects of LSD on emotional empathy. Plasma oxytocin levels were also measured. LSD dose-dependently increased implicit and explicit emotional empathy, with the highest 200 µg LSD dose having a significant effect compared with placebo. The 200 µg dose of LSD also moderately increased plasma oxytocin levels compared with placebo. Ketanserin reduced the LSD-induced elevations of oxytocin but not the LSD-induced increases in emotional empathy. These findings confirm that LSD enhances empathy, and this effect may be partially independent of its primary action on 5-HT2A receptors to induce subjective psychedelic effects. In contrast, LSD-induced oxytocin release may depend on 5-HT2A receptor stimulation, which is consistent with the psychedelic effect of LSD. Further studies are needed to investigate whether LSD may also enhance empathy and potentially produce therapeutic effects in patients who have deficits in empathy and impairments in social functioning.